Polymerase chain reaction for detection of Toxoplasma gondii - Savva, D.; Morris, J. C.; Johnson, J. D.; Holliman, R. E. (Journal of Medical Microbiology, 1990)
Summary A DNA-based assay has been developed for the detection of Toxoplasma gondii. The assay makes use of the polymerase chain reaction (PCR) to amplify part of the P30 gene on the parasite’s DNA. Following gel electrophoresis, the amplified DNA can be detected either directly on the gel or by Southern hybridisation with radioactive or non-radioactive DNA probes. The assay has been used to detect the DNA from different isolates of T. gondii in a background of human or mouse DNA. Together with other information such as clinical data, CT scans and serology, the PCR assay should improve the diagnosis of toxoplasmosis in immunosuppressed and immunocompromised patients as well as in fetal tissues.